Sistem Pendukung Keputusan Seleksi Guru Teladan di SMP N 2 Loli Menggunakan Metode SAW (Simple Additive Weighting) - Anderias Jowa; Adelbertus Umbu Janga; Alexander Talo Popo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Decision Support Sistem (DSS) for selecting exemplary teachers at SMP Negeri 2 Loli aims to assist the school in determining teachers who deserve to be recognized as exemplary teachers. The evaluation of exemplary teachers involves various criteria such as teaching performance, discipline, creativity, and communication skills with students. However, the selection process conducted manually tends to be subjective and time-consuming. Therefore, a sistem is needed to simplify and accelerate the selection process while producing objective and transparent results. This sistem is developed using the Simple Additive Weighting (SAW) method, which is one of the techniques in multi-criteria decision-making. The SAW method works by assigning weights to each predetermined criterion and calculating the weighted scores for each alternative (teacher). These weighted scores are then summed to determine the ranking order of teachers who meet the criteria as exemplary teacher candidates. The results of this study indicate that the implementation of the SAW method can produce a more structured, objective, and efficient exemplary teacher selection process. The sistem facilitates the school in conducting evaluations and decision-making, while also reducing the potential for errors that may occur during manual selection. Thus, this decision support sistem is expected to make a significant contribution to improving the quality and accuracy of exemplary teacher assessments at SMP Negeri 2 Loli.